A Review of the Literature on The Impact 0f Weight Training on The Elderly's Fat Free Mass Index - Alam, Ikbal Gentar; Abdillah, Muhammad Ihsan; Mukti, Agus; Fitri, Rahma Nurwiati; Adeulien, Ziyyan Nazhira; Fadlyllah, Arya Fuad (Universitas Pendidikan Indonesia (UPI), 2023)
Elderly people's health and quality of life may suffer if their muscle mass declines and their fat mass increases. It is well established that weight training is a useful strategy for gaining muscle mass and losing body fat, but further research is needed to determine how it affects FFMI in senior citizens. In order to determine how weight training affects.To identify the effect of weight training on fat-free mass index (FFMI). To identify the effect of weight training on fat-free mass index (FFMI), we used a literature review as a guide to search for research articles obtained from the internet using the PubMed site. Analysis of the five selected research articles showed that weight training can increase fat-free mass index in the elderly. The result of this literature review article is that weight training has an influence on increasing or maintaining FFMI in the elderly. The result in this literature review article is that weight training has an influence in increasing or maintaining FFMI in the elderly. The ideal exercise program for the elderly is regular exercise 2-3 times per week. For weight training in the elderly, it is better to use a professional trainer in order to prevent injury and maximize benefits. Balanced nutritional intake is also very necessary in the process of weight training for the elderly. Meanwhile, if you do not do weight training, it can reduce FFMI in the elderly. It it is explained that the group that was not given a weight training program, did not experience an increase in FFMI.